Effect of storage methods and seed rhizome treatment on the field performance of ginger - Y A Lyngdoh, A Shadap, N K Hegde, (Journal of Spices and Aromatic Crops, 2015)
An experiment was conducted to evaluate the effect of different storage methods and seed rhizome treatment on the field performance of ginger var. Humnabad. Four storage methods were selected for the study viz., rhizomes kept in sand layers (indoor), 250 gauge polyethylene bag with 0.5% vents (indoor), Zero energy cool chamber (ZECC) either in open condition or in polyethylene bag with 0.5% vents. The seed rhizomes were treated with fungicide viz., Ridomil MZ (3 g L-1), bio-control agent Trichoderma harzianum (5 g kg-1 seed rhizome) and no seed treatment as the control. Highest germination (98.89%), plant height (52.3 cm), leaf area index (25.75), number of tillers clump-1 (19.7), pseudostem girth (3.41 cm) and fresh rhizome yield (22.35 t ha-1) were recorded in rhizome stored in ZECC treated with T. harzianum whereas, the rhizome stored in sand layer with no seed treatment recorded the lowest levels of germination (75.56%), plant height (33.6 cm), leaf area index (9.73), number of tillers clump-1 (12.6), pseudostem girth (2.32 cm) and fresh rhizome yield (11.84 t ha-1).